A biallelic variant in IQCE predisposed to cause non-syndromic post-axial polydactyly type A - Muhammad Bilal; Muhammad Raheel; Gul Hassan; Shah Zeb; Arif Mahmood; Zamrud Zehri; Hafiza Yasmin Manzoor; Muhammad Umair (Journal of Biochemical and Clinical Genetics)
Background: Polydactyly or hexadactyly is a familiar limb defect that either occurs as an isolated entity (non-syndromic) or is associated with severe (syndromic) morphological phenotypes. Generally, it appears due to a defect in the anteroposterior patterning during limb development. Methods: Here, we present a proband having non-syndromic post-axial polydactyly (PAP) evaluated using whole exome sequencing followed by Sanger sequencing. Furthermore, 3D protein modeling was executed for the normal and mutated IQ domain-containing protein E (IQCE) gene. Results: WES analysis revealed an already reported bi-allelic variant (c.395-1 G>A) in the IQCE gene, previously associated with PAP 7. Furthermore, 3D modeling revealed significant fluctuations in the IQCE protein secondary structure, thus affecting downstream signaling. Conclusion: The work presented validated the significant role of the IQCE gene in the development and patterning of human limbs. [JBCGenetics 2023; 6(1.000): 29-35]